PELAYANAN BIMBINGAN ROHANI ISLAM DALAM MENGURANGI TINGKAT STRES PADA PASIEN KEGUGURAN DI RUMAH SAKIT ST. MADYANG PALOPO - Alfina Mika Damayanti; St. Rahmatiah; Sattu Alang (Jurusan Bimbingan dan Penyuluhan Islam, 2022)
The journal aims to describe how Islamic spiritual guidance ministry takes shape. This research uses a type of descriptive qualitative research located at St. Madyang Palopo Hospital. The research approach used is the Islamic spiritual guidance approach. The primary data sources of this writing are Rahmi as an Islamic spiritual guide (key informant), and additional informants, namely Sri (midwife) Widya Arini, Dian, Suci, Rina, Sukma (miscarriage patient). Secondary data sources are books, theses, journals, literature, and other data sources that can be used as a complement. The methods of data collection are observation, interviews, and documentation. Data analysis is carried out in three stages, namely data reduction, data presentation, and drawing conclusions. Based on the results of this study, the form of Islamic spiritual guidance services for miscarriage patients at St. Madyang Palopo Hospital is religious guidance, which includes assessment, counseling, diagnosis, therapy or treatment, and evaluation. This guidance service is carried out before and after surgery. Supporting factors are the individual (oneself) and the support of the family. The inhibiting factors are the lack of spiritual guidance and inadequate facilities.